Scythe fencing in “Bartoszowe Troops” – the first original Polish school of martial arts (1903-1914) - Zaborniak, Stanisław; Bąk, Robert; Niewczas, Marta (ARCHIVES OF BUDO, 2017)
The use of scythes in hand-to-hand fighting against regular enemy soldiers is an original Polish martial arts dating back to the turn of the 18th and 19th century. The goal of this review is to study three issues: (1) general knowledge about the historical context in which the so-called battle scythe was used by Polish peasants and about effectiveness of this weapon; (2) use of this original martial arts and the memory of heroic deeds performed by Bartosz Głowacki troop in order to brace patriotic, moral and physical values, in particular among Polish youth at the turn of 19th and 20th century, being an important part of the strategy adopted in order to regain independence; (3) description of motor properties exhibited during scythe fencing as an original form of martial art training. It is believed that scythe could have been used in 1036-1037 during the peasant uprising. It was used during a fight at Orsza in 1514 and certainly during the Battle of Obertyn in 1531. In the 17th century, shepherds and the Zaporozhian Cossacks fought using scythes. Bartosz Głowacki troop proved that fighting with this original weapon is effective during the Battle of Racławice (one of the first battles that took place during the Kościuszko Uprising against Russia on 4 April 1794). “Bartoszowe Troops” which followed patriotic traditions and made scythe fencing more attractive supported the independence aspirations exhibited by the rural youth. Together with the Polish Riflemen’s Association founded by Józef Piłsudski, the “Falcon” Polish Gymnastic Society and the Polish Rifle Squads, these troops formed Polish paramilitary movement established at the Austrian Partition before the First World War. Documentation preserved allows us to reconstruct this unique martial art regarding its motor properties. Similarities in this respect (also taking weapon length into account) may be noticed in the case of naginata (one of the Japanese budō arts), Portuguese jogo do pau, elements of Chinese wushu or Indian kalripayat. Fortifying contemporary martial arts with various techniques using original weapons the basic application of which did or does not involve armed combat (such as scythe in this article) may have broad application in cultural diversity and health promotion. In spite of appearances, health-related training based on selected martial arts combined with martial arts bibliotherapy and other methods of innovative agonology may have a positive impact on all health dimensions (somatic, mental, social health) and increase the attractiveness of survival ability
Keywords: Galicia (in Poland); The “Falcon” Polish Gymnastic Society; Innovative agonology; Martial arts bibliotherapy